Stabilization of enzymatically polymerized 2,4 dichlorophenol in model subsurface geomaterials - Palomo, Monica (Kansas State University, 2008)
Human activities generate large amounts of chlorinated phenolic chemicals that are often introduced into the soil environment during pesticide and insecticide application, industrial releases, and accidental spills. For example, 2,4-dichlorophenol (DCP), a derivative of the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) can been found in soil within 24 hours of 2,4- D application. Horseradish peroxidase (HRP)-mediated polymerization has been proposed as an approach to remediate soils and groundwater contaminated by phenolic pollutants. Treatment with HRP results in the transformation of phenols into polyphenolic oligomers that sorb strongly or precipitate on soils surfaces. Although HRP-mediated chlorophenol stabilization has been studied extensively in surface soils, very limited scientific data is available that supports the application of this technology in subsurface materials. Hence, the focus of this study was to evaluate sorption and binding of DCP and products of HRP-mediated polymerization of DCP to model geosorbents representing subsurface geomaterials. These sorbents included two humin-mineral geomaterials and one mineral geosorbent derived from surface soils. Soil-water phase distribution of total solute in the HRP-amended systems was observed to reach equilibrium within 7 days in woodland humin-mineral soil (WHM), and within 1 day in agricultural humin-mineral (AHM) and model mineral geomaterials. For all the geomaterials used, water extraction data indicated the development of contact time-dependent resistance to extraction/dissolution of soil-associated DCP and DPP. Solute associated with WHM geomaterial was higher at the end of the study than that associated with AHM. Contact time increased DCP stabilization at all initial aqueous DCP concentrations studied. Results of this study suggest that DCP stabilization in organic geosorbents results from a combination of sorption and cross-coupling of DCP and precipitation of DPP; in inorganic soils, precipitation of DPP macromolecules is the dominant process. HRP-mediated stabilization of DCP in soils was effective and independent of the solution ionic concentration. The amount of DCP stabilized in the mineral soil was comparable to that stabilized in humin-mineral geomaterials. The research reported in this dissertation demosntrates the potential of HRP enzyme to stabilize DCP in subsurface geomaterials under variable contaminant and salt concentrations, thereby restricting its transport in the environment.
Keywords: Stabilization; 2,4-dichlorophenol; Horseradish peroxidise; Polymerization; Geomaterials; Engineering, Civil (0543); Engineering, Environmental (0775)